Determination Of Banking Profitability In Indonesia - Devie Yanti; Yuliani Yuliani; Kemas Muhammad Husni Thamrin (UNIVED Press, 2025)
This study aims to analyze the determinants that affect banking profitability in Indonesia, as low profitability will reduce banks' ability and willingness to finance the broader economy and difficulties in facing the challenges of an unstable global economy. The population of this study is Conventional Commercial Banks in Indonesia from 2014 to 2023. The sampling technique uses the purposive sampling technique so that 51 research data are obtained. The research analysis used panel data regression and its significance level was 5%. The results of a study of 51 Conventional Commercial Banks in the period 2014-2023 show that the non-performing loan (NPL) ratio has a negative impact on banking profitability (ROA), the liquidity ratio (LDR) has a negative impact on banking profitability (ROA), the capital adequacy ratio (CAR) has a negative impact on banking profitability (ROA), and the operating expense ratio (BOPO) has a positive impact on corporate profitability (ROA).